2019
DOI: 10.2217/fon-2018-0912
|View full text |Cite
|
Sign up to set email alerts
|

Guidance of Sentinel Lymph Node Biopsy Decisions In Patients With T1–T2 Melanoma Using Gene Expression Profiling

Abstract: Aim: Can gene expression profiling be used to identify patients with T1–T2 melanoma at low risk for sentinel lymph node (SLN) positivity? Patients & methods: Bioinformatics modeling determined a population in which a 31-gene expression profile test predicted <5% SLN positivity. Multicenter, prospectively-tested (n = 1421) and retrospective (n = 690) cohorts were used for validation and outcomes, respectively. Results: Patients 55–64 years and ≥65 years with a class 1A (low-risk) profile had SLN positivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 40 publications
(76 reference statements)
0
55
1
Order By: Relevance
“…Similarly, two recent prospective studies (consisting primarily of AJCC stage I/II patients) found GEP class to be the strongest predictor of both local recurrence and distant metastasis [8,9]. Finally, in a study of 1421 prospectively tested T1/T2 tumor stage patients – most undergoing SLNB – from 26 centers, GEP class was a significant predictor of SLNB-positivity [10]. The 31-GEP test is now covered by Centers for Medicare and Medicaid Services for patients over age 65 with T1a (with adverse features), T1b and T2 tumors.…”
Section: Prognostic Gep Tests For Melanomamentioning
confidence: 93%
“…Similarly, two recent prospective studies (consisting primarily of AJCC stage I/II patients) found GEP class to be the strongest predictor of both local recurrence and distant metastasis [8,9]. Finally, in a study of 1421 prospectively tested T1/T2 tumor stage patients – most undergoing SLNB – from 26 centers, GEP class was a significant predictor of SLNB-positivity [10]. The 31-GEP test is now covered by Centers for Medicare and Medicaid Services for patients over age 65 with T1a (with adverse features), T1b and T2 tumors.…”
Section: Prognostic Gep Tests For Melanomamentioning
confidence: 93%
“…As Cam_121 was developed and tested on the same dataset, there are chances of overfitting. Therefore, we further tested the signatures’ prognostic power in an externally acquired independent validation dataset from the Leeds Melanoma Cohort (n=677) (15). This confirmed that Cam_121 was associated with melanoma-specific survival (MSS) in both univariate (HR=1.49 (95% CI 1.27-1.74), p=5×10 −7 ) and multivariate Cox regression models (HR=1.7 (95% CI), p=0.001, Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Building on these data, Gerami et al first reported a prognostic gene expression profile (GEP) test utilising the 31-gene panel (28 discriminating and 3 control genes) for use in patients with CM (Decision-Dx Melanoma™) (12). The test measures the expression of individual genes from formalin-fixed paraffin-embedded (FFPE) primary melanomas to provide a binary classification of low (class 1) or high (class 2) risk for developing metastases within 5 years of diagnosis (with A and B subclasses to further stratify risk) (13-15). A further recent unsupervised clustering analyses based on 677 primary melanoma transcriptomes embedded within a population-controlled cohort study from the Leeds Melanoma Cohort (LMC) identified a six-class 150-gene prognostic signature (herein reference to as LMC_150) (16).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the NCCN does not recommend SLNB in patients whose risk for a positive finding is <5% (T1a and below); however, they do recommend offering SLNB in the appropriate clinical setting when the risk is 5%-10% (T1b lesions). 5,6 , 7…”
Section: Introductionmentioning
confidence: 99%
“…The 31-GEP seeks to identify those T1 and T2 tumors with genetic signatures that are likely to behave in either low-risk or high-risk manners with regard to recurrence, distant metastasis, and mortality. 6,8-11 This test stratified patients into 4 groups: Class 1A (considered low risk of metastasis or recurrence), Classes 1B and 2A (intermediate risk), and Class 2B (high risk). When these groups are further broken down by patient age, it becomes apparent that patients >55 years of age whose tumors are Class 1A have <5% incidence of SLNB positivity.…”
Section: Introductionmentioning
confidence: 99%